Blood routine reference value range should be adjusted according to regional and ethnic characteristics - Guo, Yan; Liu, Xiao; Zihao, Zhang; Zhang, Qiang; Shi, Zhongshan; Zhang, Na (Frontiers in Public Health, 2022)
Objective: To further understand the influence of regional and ethnic factors on blood routine indicators. Methods: The routine blood test (RBT) results of 617 healthy men aged 18–45 years old of the Li, Tibet, and Han nationalities living in the city of Sanya, Hainan Province (200 m), the city of Xining, Qinghai Province (2300 m), and Maduo County of Qinghai Province (4300 m) for a long time were studied. Eight indexes, such as the red blood cell (RBC), hemoglobin (Hb) and platelet (PLT) counts, were compared and analyzed. Results: With an increase in altitude, the RBT index values and change trends of the different ethnic groups were different. When the altitude increased by 2000 m, the RBC and Hb increased by 6.6% and 8.1%, respectively, and the PLT decreased by 16.8%. However, the RBC, Hb, and PLT of the Tibetan subjects decreased by 7.4%, 5.1%, and 3.0%, respectively. In the same region, there were also significant differences in the RBT index values among the ethnic groups. The RBC increased, Hb decreased, and PLT did not change in the Li nationality in Sanya compared with the Han nationality. The RBC, Hb, and PLT of Tibetans in the Xining area were significantly higher than those of the Han population. Referring to the current RBT reference value range in China, the abnormal rates of the various RBT index values of the enrolled population were high. By utilizing Hb as an example, 27.7% of the Li nationality in Sanya was low, 67.0% of the Tibetan nationality in Xining was high, and 89.4% of the Maduo Han nationality was high. The PLT was lower in the Sanya Li nationality (13.8%) and the Maduo Han nationality (88.3%). Conclusion: Regional and ethnic factors have a significant impact on the RBT, and the current range of normal values of the RBT in China needs to be revised and adjusted.